Social media exposure to adolescent sexual behavior - Ema Waliyanti; Afifah Aristawidya (Journal of Health Technology Assessment in Midwifery, 2025)
The Indonesian Child Protection Commission in 2022, stated that 96% of children aged 10-17 years in Indonesia had opened negative content (pornography) with an average of 64 hours of use per month for 4,500 junior and senior high school students. The increasing interest of adolescents in sexual issues encourages them to seek information about sexuality through various media. This study aimed to examine the association between the extent of social media use and adolescents’ involvement in risky sexual behaviors. The population in this study were all eight grade students, with a sampling technique using purposive sampling with a total of 82 people based on the inclusion criteria, namely adolescents who actively use social media and are willing to be research respondents. Data collection was carried out using a closed questionnaire consisting of two parts, namely a social media use questionnaire and a questionnaire on risky sexual behavior in adolescents. The research instrument was prepared by the researcher based on relevant theories and tested for validity and reliability using the Cohen's Kappa test. Data analysis was carried out using the Chi-Square test to determine the relationship between social media use and risky sexual behavior in adolescents .The results showed that social media use was in the low category of 49 people (59.8%) and risky sexual behavior in the medium category of 64 people (78%). Statistical tests showed that there was a relationship between social media use and risky sexual behavior in adolescents with a p value of 0.000 (p<0.05). There is a relationship between social media use and risky sexual behavior in adolescents. Adolescents are expected to be able to use social media wisely and avoid pornographic content.